STRATEGI REKRUTMEN PESERTA DIDIK BARU DALAM MASA PANDEMI COVID-19 DI SMK DARUSSALAM - Eko Budiywono; Liya Kholifatus Sholekhah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
In 2019 the world was stirred up by the Covid-19 outbreak originating from Wuhan, China, entering Indonesia at the end of February, this epidemic was so very disturbing because the transmission was so fast and invisible. All learning mechanisms during this pandemic were different from the previous year. But all of that did not dampen the interest of prospective students to register at SMK Darussalam Blokagung the researchers suspected that there was a strategy applied in the recruitment of new students. The research problem was the strategy of recruiting new students and the supporting factors that hindered the Covid-19 pandemic. The subject of the research was the principal of the school. and WKS. Kesiswaan as chairman of the PPDB committee. Qualitative research methods, data collection methods of observation, interviews and documentation, data analysis using an interactive model of Miles Hubermen and data validity using triangulation. The results of the study: the strategies used were promotion strategies and selection strategies. The supporters included teachers, students and alumni, all media. by SMK Darussalam Blokagung.